PLURALISME DALAM FILM DOKUMENTER BETA MAU JUMPA (ANALISIS SEMIOTIKA JOHN FISKE) (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2021)
This study aims to determine the use of pluralism message signs in the documentary film "Beta Mau Meet" and to find out the meaning of pluralism messages in the documentary film "Beta Mau Jumpat". This type of research is descriptive qualitative using John Fiske's semiotic analysis method with three stages of level analysis, namely reality, representation and ideology. The results of the study indicate that there are seven sign scenes that support pluralism in the Beta Mau Jumpa documentary. These seven scenes show the struggle of young people and the women's movement against segregation or class separation that occurred in Ambon, although the armed clashes have ended, the hate narrative is still ongoing and can affect the next generation. the meaning of pluralism in this film refers to maintaining the balance of the principles of humanism, recognizing and respecting the existence of other religions, and freedom of religion. From this, the researcher concludes that understanding differences accompanied by knowledge and understanding in society will create a harmonious relationship.